Compulsory Psychiatric Admission in a Patient With Metastatic Breast Cancer: From Palliative Care to Assisted Suicide - Noppes, Felix; Savaskan, Egemen; Riese, Florian (Frontiers in Psychiatry, 2020)
The provision of palliative care in psychiatry and the use of coercion in palliative care are underexplored areas. We report the case of a 65-year-old woman with cerebral metastatic breast cancer who was compulsorily admitted from a specialized palliative care ward to a psychiatric inpatient ward in Zurich, Switzerland. While in specialized inpatient palliative care, the patient had resisted palliative care but was found to lack decision-making capacity for her treatment due to disordered thought process and paranoid delusions. Under our care, which involved coercive treatment in the form of concealed administration of an antipsychotic, the patient’s psychiatric symptoms improved. She regained decision-making capacity, was granted discharge from hospital and ended her life by assisted suicide on the day of discharge.